Competition in the ancient world - Fisher, N. R. E. (Nicolas Ralph Edmund); Wees, Hans van (Classical Press of Wales, The, 2010)
Ancient peoples, like modern, spent much of their time engaged in or thinking about competition. Organised competitions - with rules, audiences and winners - included the Olympic and gladiatorial games. Informal, indefinite, often violent, competition involved fundamental goals such as power, wealth and honour. The ten new studies in this book treat ancient Greece and Rome, but also the earliest human societies, and the Assyrian and Aztec empires. Together they make a case for viewing competition for superiority not as 'peculiarly Greek' but as a major driving force in ancient history.